Fighting over the Archive: Politics and Practice of the Art World in Angola - Sousa, Suzana (Kronos: Southern African Histories, 2019)
If the ambivalent figure of the nation is a problem of its transitional history, its conceptual indeterminacy, its wavering between vocabularies, then what effect does it have in narratives and discourses that signify a sense of ‘nationness’: the heimlich pleasures of the heart, the unheimlich terror of the space or race of the Other; the comfort of social belonging, the hidden injuries of class; the customs of taste, the powers of political affiliation; the sense of social order, the sensibility of sexuality; the blindness of bureaucracy, the strait insight of institutions; the quality of justice, the common sense of injustice; the langue of the law and the parole of the people.